AAV-mediated co-expression of an immunogenic transgene plus PD-L1 enables sustained expression through immunological evasion - Travis B. McMurphy; Andrew Park; Patrick J. Heizer; Crystal Bottenfield; James H. Kurasawa; Yasuhiro Ikeda; Michael R. Doran (Scientific Reports)
Abstract Adeno-associated virus (AAV) vectors can mediate long-term expression of immunogenic transgenes in vivo through transduction of tolerogenic cells in the liver. Tissue-targeted AAV vectors allow transduction of non-hepatic cells, but this necessitates development of strategies to minimize transgene immunogenicity. Here, we first validated that AAV capsids with tissue-specific tropism and transgene promoters enabled expression of the immunogenic protein, firefly luciferase, in liver, muscle, or adipose tissue. Cellular immunity was detectable in animals where luciferase was expressed in muscle or adipose, but not liver tissue. With the objective of enhancing tolerance of transduced non-hepatic cells, AAV vectors were engineered to co-express luciferase plus the immune checkpoint protein, PD-L1. In animals where transduced cells expressed luciferase but not PD-L1, there was incremental depletion of transduced cells over time. By contrast, the bioluminescent signal increased incrementally over the study, and was significantly greater, in the muscle and adipose tissue of animals where PD-L1 was co-expressed with luciferase. Our data demonstrate that PD-L1 co-expression facilitates persistent, tissue-targeted expression of immunogenic transgenes without transducing tolerogenic hepatic cells. Our strategy of PD-L1 co-expression may provide a versatile platform for sustained expression of immunogenic transgenes in gene and cell therapies.